Analisis Biaya Signifikan Consumable Material Pada Struktur Bangunan Gedung Menggunakan Metode Pareto - Putra, Muhammad Nanda Arya; Gawei, Apria Brita Pandohop (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2026)
The construction sector faces challenges in material cost management in reinforced concrete structural work due to large budget absorption and the risk of waste in conventional calculations as well as the high risk of material waste. This study aims to identify the types of consumable materials included in the category of materials with significant costs in building structures in the Kalibata Elementary School Development Project, Palangka Raya City, for eight months from August 2025. Using the Pareto Method with a quantitative approach through a case study method. This study integrates secondary data including DED drawings, AHSP 2025, and Basic Price Palangka Raya Semester II 2025 into BIM objects through the Shared Parameters feature for precise data extraction and Pareto Analysis. The results show that the total cost of structural material consumables reached Rp 1,747,929,555,300. Through the Pareto diagram, five main materials were identified that absorbed 79.393% of the total budget, namely Ø 16 mm threaded rebar (18.402%), Ø 10 mm plain rebar (17.356%), Portland cement (16.008%), gravel (14.398%), and dolken wood Ø 8-10 cm (13.120%). These five materials are at the cumulative threshold of 80% of the total cost of consumable materials, so their use is the main key to minimizing material waste and optimizing the profitability of construction projects.